1999
DOI: 10.1002/hep.510290302
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular Intrahepatic Portosystemic Shunt: Short–Term and Long–Term Effects on Hepatic and Systemic Hemodynamics in Patients With Cirrhosis

Abstract: The aim of this prospective, nonrandomized study was to assess the short-and long-term effects of transjugular intrahepatic portosystemic shunt (TIPS) on hepatic and systemic hemodynamics and on gastroesophageal collateral flow in patients with cirrhosis and failure of chronic sclerotherapy. Cardiac output (CO), free and wedged pulmonary artery pressure (FPAP and WPAP), systemic vascular resistance (SVR), azygos venous blood flow (AzVBF), and the relative (portal minus vena cava) pressure in the portal vein (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 34 publications
0
50
0
3
Order By: Relevance
“…Further, pulmonary arterial pressure is increased that may further contribute to enlargement of RV dimension. Upon liver transplantation, both the portosystemic shunt and pulmonary arterial pressure will be reduced that may partly explain the reduction in RV dimension [25]. Future prospective studies are nonetheless required to discern the underlying mechanism for RV dimension reduction following liver transplantation.…”
Section: Discussionmentioning
confidence: 95%
“…Further, pulmonary arterial pressure is increased that may further contribute to enlargement of RV dimension. Upon liver transplantation, both the portosystemic shunt and pulmonary arterial pressure will be reduced that may partly explain the reduction in RV dimension [25]. Future prospective studies are nonetheless required to discern the underlying mechanism for RV dimension reduction following liver transplantation.…”
Section: Discussionmentioning
confidence: 95%
“…Immediately after the procedure, in fact, the amount of blood reaching the heart increases rapidly, and a rise in the right atrium and the central venous pressure has already been described [2]. This value does not remain stable over time [3,4]; it is therefore possible that a reduction of 25% in the PPG value measured immediately after TIPS may not be the same a few days or weeks later. We therefore wonder whether the authors have some evidence that the PPG value reached immediately after TIPS opening had remained stable over time.…”
mentioning
confidence: 90%
“…Bernd Saugel et al [22] reported that the TIPS procedure led to a significant increase in serum bilirubin level, ALT and AST levels, and INR level as well. Earlier studies [23,24] reported that TIPS can result in a deterioration of the liver function in the form of elevation of bilirubin, ALT and AST, probably due to reduction of hepatic blood flow and sinusoidal blood flow resulting from diversion of portal blood through a TIPS, which is even more obvious in patients with advanced liver disease due to incomplete hepatic artery buffer response [25] . Compatible with these studies, our study showed that TBIL, PT, INR, and ALT and AST levels had significantly increased after TIPS in group A, but ALT and AST levels normalized by the 1st month posttreatment.…”
Section: Discussionmentioning
confidence: 99%